2008
DOI: 10.1016/s0072-9752(07)01255-9
|View full text |Cite
|
Sign up to set email alerts
|

“Pre‐symptomatic” Huntington's Disease

Abstract: Publication of the human genome has accelerated the paradigm shift in medicine from treatment of disease following diagnosis to the prediction and prevention of disease in healthy persons. Huntington's disease (HD), an autosomal dominant progressive neurological disease with an identified gene mutation (Huntington's Disease Collaborative Research Group, 1993), could prove to be a useful model in preparing for preventive clinical trials in other neurodegenerative diseases because individuals with the gene expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…For instance, recent results suggest that obsessive compulsive symptoms in prHD emphasize worrying and checking and rarely reach the levels of severity associated with diagnoses of obsessive compulsive disorders [101] until later in HD following clinical diagnosis [113]. Similarly, an analysis of the depression phenotype in prHD suggests that cognitive difficulties (poor concentration), suicidal thoughts, and low energy characterize this syndrome [21, 102, 115]. Although the range of scores on traditional depression assessment seen in prHD was often as broad as that seen in Major Depressive Disorder (MDD), the profile of these scores was poorly related to overall severity of depressive symptoms (suggesting poor discriminative properties) and appeared distinct from that seen in MDD [117].…”
Section: Psychiatric Aspectsmentioning
confidence: 99%
“…For instance, recent results suggest that obsessive compulsive symptoms in prHD emphasize worrying and checking and rarely reach the levels of severity associated with diagnoses of obsessive compulsive disorders [101] until later in HD following clinical diagnosis [113]. Similarly, an analysis of the depression phenotype in prHD suggests that cognitive difficulties (poor concentration), suicidal thoughts, and low energy characterize this syndrome [21, 102, 115]. Although the range of scores on traditional depression assessment seen in prHD was often as broad as that seen in Major Depressive Disorder (MDD), the profile of these scores was poorly related to overall severity of depressive symptoms (suggesting poor discriminative properties) and appeared distinct from that seen in MDD [117].…”
Section: Psychiatric Aspectsmentioning
confidence: 99%
“…Several aspects of HD may also give insights into concerns of family carers, and how some concerns may not be shared by carers in other conditions. Manifestations of HD in the earliest phases of the condition, prior to the onset of motor symptoms, have only recently been described (Duff et al. 2008, Paulsen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects of HD may also give insights into concerns of family carers, and how some concerns may not be shared by carers in other conditions. Manifestations of HD in the earliest phases of the condition, prior to the onset of motor symptoms, have only recently been described (Duff et al 2008, and the impact of changes in the cognitive and behavioural domains may be apparent in dayto-day functioning long before actual diagnosis. This is difficult for family members who search for explanations of changes in behaviour such as irritability or forgetfulness, but don't know if these are due to HD, other health problems, or a result of something that the family member did to upset the person .…”
Section: Unique Hd Family Carer Concernsmentioning
confidence: 99%
“…Many studies have documented the deleterious effect HD has on the brain, (for review see: [3]). Furthermore, it has been shown that presymptomatic (Pre-HD) subjects may have brain atrophy up to 10 years before disease manifestation [4], [5]. However, less is known about the effects of HD on white matter (WM) fibers.…”
Section: Introductionmentioning
confidence: 99%